Creating and Collaborating: Students’ and Tutors’ Perceptions of an Online Group Project - Donelan, Helen; Kear, Karen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Although collaboration skills are highly valued by employers, convincing students that collaborative learning activities are worthwhile, and ensuring that the experience is both useful and enjoyable, are significant challenges for educators. This paper addresses these challenges by exploring students’ and tutors’ experiences of a group project where part-time distance learners collaborate online to create a website. Focus groups were conducted with students who had recently completed the project, and discussion forums were used to gather feedback from tutors who supported students and marked their group work. The research showed that students’ attitudes towards the group project on completion were generally favourable. Findings highlighted key aspects for successful online group projects and for motivating students to participate fully. These included: the design of authentic tasks, with skills development relevant to the workplace; careful attention to how the group work is assessed; and enabling students to develop websites they could be proud of. Frustrations for students were associated with the lack of engagement of fellow students and with limitations of the tool provided for building the website. Tutors found marking the work a time-consuming and complex process. Tutors were also unconvinced of the value and fairness of assessing students partly on a group, as opposed to an individual, basis.